Investigation of the computational complexity of methods for hiding information in cluster steganosystems - Shekhanin, K.Yu.; Pshenichnaya, S.V.; Kuznetsov, A.A. (Radiotekhnika, 2021)
Several methods of technical steganography are currently known. Hiding information in a model in 3D printing, this industry of hiding information has certain advantages and disadvantages, namely: the relatively high cost of creating a hidden message and the difficulty in reading the information. The second area of technical steganography is related to network traffic. In this method, information can be hidden, for example, in the header fields of protocols, or, for example, the transmission of a hidden message by sending packets in a certain sequence. There are also methods of hiding information in the structure of the file system, but the known methods are either capable of hiding a small amount of information, or have an insufficient level of resistance to detection. Thus, an urgent task is to develop a method for hiding information, which is able to hide more information and has a higher level of resistance to detection, with a satisfactory level of computational complexity. This paper presents methods of technical steganography based on the structural features of file systems in storage media, in particular, hiding information in the FAT file system by mixing clusters of certain key files (cover files). Methods of hiding information in the structure of a clustered file system by mixing clusters of cover files require significant computational resources. In this paper, research has been carried out on methods to increase computational efficiency in terms of the amount of required RAM, and the number of the required number of basic operations to hide a message.